Determining the traditional methods used by newborn women by giving birth: a descriptive study - Bülez, Aysel; Sönmez, Mehtap; Orhan, Merva; Güneş, Aygül (The European Research Journal, 2023)
Objectives: This study was carried out to determine the traditional practices that women who have just given birth apply to their babies. Methods: The research is descriptive. The participants were recruited from women who had just given birth to 198 women in a maternity hospital. The data was collected through the personal information form. The chi-square test was used to plan the categorical data in detail as the mean of the research data, as numbers, and as percentages. p < 0.05 was accepted as meaning. Results: It was determined that traditional practices frequently used by women; The use of the yellow blanket against jaundice, swaddling so that the waist does not sink in, staying warm, being hard as steel, and having straight legs and the use of salt. It was determined that these practices were applied more by mothers who graduated from primary school. Although the frequency of use of applications such as burying the belly in the garden and throwing it in the water was found to be significant by age, it was determined to be used more in the group aged 31 and over. It has been determined that wearing evil eye beads is more common among mothers under the age of 25. Conclusions: In our study, it was observed that traditional practices were widely applied in the neonatal period. Newborn health should be supported by providing continuous midwifery care to women, education, and health checks.